(untitled) (Jóvenes en la Ciencia, 2024)
The menstrual cycle can be affected by many factors, in the nursing work area, stress is a dominant factor in affecting the menstrual cycle, currently a high relationship has been found between high stress, anovulation and menstrual cycles. longer, as well as menstrual pains. These conditions can also be caused by work schedules in nurses who work rotating shifts and night shifts. The objective of this work was to identify whether work causes a condition in the menstrual cycle in nursing staff. Descriptive, cross-sectional and retrospective study. A sample of 26 nurses was used at the convenience of the general hospital of Irapuato and Salamanca, who work the morning shift. They were given a survey with 12 questions about menstruation and its relationship with work stress. It was shown that 85% of the nurses who responded stated that stress contributes to menstrual pain. These results suggest that stress it is a negative factor that affects the alteration of the menstrual cycle.